Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/cells11121929
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling of CHO Cells during the Production of Biotherapeutics

Abstract: As indicated by an ever-increasing number of FDA approvals, biotherapeutics constitute powerful tools for the treatment of various diseases, with monoclonal antibodies (mAbs) accounting for more than 50% of newly approved drugs between 2014 and 2018 (Walsh, 2018). The pharmaceutical industry has made great progress in developing reliable and efficient bioproduction processes to meet the demand for recombinant mAbs. Mammalian cell lines are preferred for the production of functional, complex recombinant protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 64 publications
(221 reference statements)
2
14
0
Order By: Relevance
“…Malate, fumarate, citrate, and succinate are secreted in the exponential phase due to high TCA cycle activity for biomass production (Coulet et al, 2022). Kuang et al ( 2021) identified new inhibitory metabolites in CHO cell cultures that affect cell growth, protein titer, and mAb glycosylation, with the secretion of these metabolites being dependent on the cellular metabolic state (Supporting Information: Table S1) (Kuang et al, 2021).…”
Section: Detection Of the Metabolic Phase Of The Culture And Phase Sh...mentioning
confidence: 99%
“…Malate, fumarate, citrate, and succinate are secreted in the exponential phase due to high TCA cycle activity for biomass production (Coulet et al, 2022). Kuang et al ( 2021) identified new inhibitory metabolites in CHO cell cultures that affect cell growth, protein titer, and mAb glycosylation, with the secretion of these metabolites being dependent on the cellular metabolic state (Supporting Information: Table S1) (Kuang et al, 2021).…”
Section: Detection Of the Metabolic Phase Of The Culture And Phase Sh...mentioning
confidence: 99%
“…During subsequent decades, different groups, including nearly every major pharmaceutical company involved in biologics development, have been developing and optimizing their own CHO‐based expression platforms. The diversity of these platforms is notable, including differences in choice of CHO cell lineages, expression plasmid constructs, gene transfer and selection methods, culture media, and cell and process engineering strategies (Coulet et al, 2022; Donaldson et al, 2022; Durocher & Butler, 2009; Reyes et al, 2022; Wurm, 2013; Wurm & Wurm, 2017). However, a common feature has been the mandatory use of stable clonal cell lines for both clinical development and manufacturing, a result of several factors including longstanding regulatory guidelines (Stuible et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Robust cell growth, elevated viable cell densities, and high product titers can be achieved through proper utilization of glucose and amino acids and their efficient/effective conversion into energy, biomass, and bioproducts. Unfortunately, the disposition of nutrients to energy or useful metabolites does not always occur in cell culture processes (Coulet et al, 2022; Ritacco et al, 2018; Young, 2013). Alternatively, metabolic inefficiencies are manifested in part as the formation of pathway intermediates and their accumulation and secretion as by‐products in cell culture over time (Pereira et al, 2018).…”
Section: Introductionmentioning
confidence: 99%